Adsorption of iron tetraphenylporphyrin on (111) surfaces of coinage metals: a density functional theory study - Tang, Hao; Tarrat, Nathalie; Langlais, Véronique; Wang, Yongfeng (Beilstein Journal of Nanotechnology, 2017)
The adsorption of the iron tetraphenylporphyrin (FeTPP) molecule in its deckchair conformation was investigated on Au(111), Ag(111) and Cu(111) surfaces by performing spin-polarized density functional theory (DFT) calculations taking into account both van der Waals (vdW) interaction and on-site Coulomb repulsion. The deckchair conformation of the molecule favours intermolecular π–π-type interactions in a less densely packed monolayer than the saddle conformation. The activation barrier between the two stable magnetic states (high spin, S = 2 and intermediate spin, S = 1) of the molecule in vacuum disappears upon adsorption on the metal surfaces. The high-spin state of physisorbed FeTPP is stable on all adsorption sites. This result reveals that an external permanent element such as a STM tip or an additional molecule is needed to use FeTPP or similar molecules as model system for molecular spin switches.
Keywords: activation barrier; density functional theory; iron tetraphenylporphyrin; spin switch; spin states